Penerapan Narasi Partisipatoris dalam Penulisan Naskah Video Dokumenter “Dari Rasi Jadi Mimpi: Langkah Menjaga Tradisi” - Edla Nabilah Elliora; Iwan Koswara; Priyo Subekti (Lembaga Pengembangan Kinerja Dosen, 2026)
This final project is entitled “Application of Participatory Narration in the Scriptwriting of the Video Documentary “Dari Rasi Jadi Mimpi: Langkah Menjaga Tradisi””. This work aims to apply a participatory narrative approach in the scriptwriting of a documentary video documentary that represents the efforts of the Kampung Adat Cireundeu community in preserving the Sunda Wiwitan tradition, particularly through the cultural practice of rasi as a symbol of identity and food self-sufficiency. The creation method employs a qualitative approach using observation, in-depth interviews, and documentation. The participatory narrative positions the indigenous community as the primary subject of the storytelling process, with the narrative constructed from the participants’ lived experiences and perspectives. The narrative structure is organized into three stages—introduction, development, and conclusion—to ensure coherence while maintaining the authenticity of the participants’ voices. The results indicate that the participatory narrative approach enhances the representation of social and cultural realities and fosters stronger audience engagement. However, this work also identifies limitations, including the dominance of certain informants, tension between expository and participatory narrative modes, and editorial compromises during the editing process. Despite these limitations, the participatory narrative approach remains relevant for documentary scriptwriting that emphasizes subject participation and the preservation of local cultural values.